2020
DOI: 10.3390/brainsci10040193
|View full text |Cite|
|
Sign up to set email alerts
|

Hippocampal and Cerebellar Changes in Acute Restraint Stress and the Impact of Pretreatment with Ceftriaxone

Abstract: Acute restraint stress (ARS) is an unavoidable stress situation and may be encountered in different clinical situations. The aim of the current study was to investigate the effects of ARS on the hippocampus and cerebellum, assess the impact of these effects on the behavior and cognitive function, and determine whether pretreatment with ceftriaxone would attenuate the damages produced by ARS on the hippocampus and cerebellum. Four groups of male mice were included in this study: The control group, ARS group, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“… BEHAVIOURAL TEST SSA COUNTRIES WITH PROVEN CAPACITY REFERENCES Forced swim test Algeria, Cameroon, Egypt, Ethiopia, Ghana, Libya, Morocco, Nigeria, South Africa ( Ngoupaye et al, 2013 , Hailu and Engidawork, 2014 ; El zahaf, N. A. and Elhwuegi, A. S, 2014 ); ( Fekadu, 2014 ); ( Merzoug et al, 2014 ); ( Ngoupaye, 2014a , Ngoupaye, 2014b ); ( Kukuia, 2015 ); ( Bikomo et al, 2017 ); ( El Brouzi et al, 2020 ); ( El-Marasy et al, 2021 ) Tail suspension test Cameroon, Ghana, Egypt, Ethiopia, Morocco, Nigeria, South Africa ( Hailu and Engidawork 2014 ; Ngoupaye, 2014b ; Kukuia et al, 2015 ; Akinpelu et al, 2017 ; Ben-Azu et al, 2018 ; Amaghnouje et al, 2020 ; Amin et al, 2020 ) Sucrose consumption preference test Algeria, Cameroon, Ghana, Nigeria, South Africa, ( Biney, 2016 , Dallé et al, 2017 ) Open field test Algeria, Cameroon, Democratic Republic of Congo, Egypt, Ethiopia, Ghana, Libya, Morocco, Nigeria, South Africa, Tanzania, Tunisia, Zimbabwe ( Manning-SayI and Leonard, 1989 , Sherif and Oreland, 1995 , Pedersen, 2008 , Okoli, 2010 , Ngoupaye et al, 2013 , Hailu and Engidawork, 2014 Merzoug et al, 2014 ; Mesfin et al, 2014 ; Ngoupaye, 2014b ; Amoateng et al, 2017 ; Bikomo et al, 2017 ; Omotoso et al, 2018 ; Miguel et al, 2019 ; Amin et al, 2020 ; El Brouzi et al, 2020 ; S...…”
Section: Introductionmentioning
confidence: 99%
“… BEHAVIOURAL TEST SSA COUNTRIES WITH PROVEN CAPACITY REFERENCES Forced swim test Algeria, Cameroon, Egypt, Ethiopia, Ghana, Libya, Morocco, Nigeria, South Africa ( Ngoupaye et al, 2013 , Hailu and Engidawork, 2014 ; El zahaf, N. A. and Elhwuegi, A. S, 2014 ); ( Fekadu, 2014 ); ( Merzoug et al, 2014 ); ( Ngoupaye, 2014a , Ngoupaye, 2014b ); ( Kukuia, 2015 ); ( Bikomo et al, 2017 ); ( El Brouzi et al, 2020 ); ( El-Marasy et al, 2021 ) Tail suspension test Cameroon, Ghana, Egypt, Ethiopia, Morocco, Nigeria, South Africa ( Hailu and Engidawork 2014 ; Ngoupaye, 2014b ; Kukuia et al, 2015 ; Akinpelu et al, 2017 ; Ben-Azu et al, 2018 ; Amaghnouje et al, 2020 ; Amin et al, 2020 ) Sucrose consumption preference test Algeria, Cameroon, Ghana, Nigeria, South Africa, ( Biney, 2016 , Dallé et al, 2017 ) Open field test Algeria, Cameroon, Democratic Republic of Congo, Egypt, Ethiopia, Ghana, Libya, Morocco, Nigeria, South Africa, Tanzania, Tunisia, Zimbabwe ( Manning-SayI and Leonard, 1989 , Sherif and Oreland, 1995 , Pedersen, 2008 , Okoli, 2010 , Ngoupaye et al, 2013 , Hailu and Engidawork, 2014 Merzoug et al, 2014 ; Mesfin et al, 2014 ; Ngoupaye, 2014b ; Amoateng et al, 2017 ; Bikomo et al, 2017 ; Omotoso et al, 2018 ; Miguel et al, 2019 ; Amin et al, 2020 ; El Brouzi et al, 2020 ; S...…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that amygdala volume was negatively and significantly correlated with scores of STAI-S and BDI in CS (29). Other findings in active CS patients revealed smaller volumes in comparison to healthy controls in gray matter of the medial frontal gyrus (32), cerebellar cortex, and gray matter volumes (33), which was observed in depression models (34). Besides, higher serum cortisol at bedtime could reflect a flatter diurnal slope (35,36), which was associated with an impaired psychological manifestation (37).…”
Section: Discussionmentioning
confidence: 81%
“…According to previous reports, there is a close association between neuro-inflammation and cognitive dysfunction caused by surgery ( 23-25 ). In the present study, cognitive function was assessed using two methods: The OFT, which has been used to detect the locomotor activity of rats ( 26 ); and the MWM test, which is a classical method to evaluate spatial learning and memory ( 27 ). The results of the present study demonstrated that surgery had no effect on the locomotor activity of rats.…”
Section: Discussionmentioning
confidence: 99%